The Primary Prevention of PTSD: A Systematic Review - Skeffington, Petra; Rees, Clare; Kane, Robert (Routledge, 2013)
There has been abundant research targeting the secondary and tertiary prevention and treatment of posttraumatic stress disorder (PTSD), including different forms of debriefing, treatments for acute stress disorder, and targeted intervention strategies (M. T. Feldner, C. M. Monson, & M. J. Friedman, 2007). However, there remains a scarcity of research pertaining to the primary, pretrauma prevention of PTSD. A systematic review was conducted in order to identify and synthesize all programs aimed at the primary prevention of PTSD to date. A broad search strategy was used, yielding 15,014 studies in 4 languages published between 1915 and 2012. Studies in which a resilience-building intervention was delivered prior to a potentially traumatic event, with data collected regarding psychological well-being, were eligible. A total of 7 studies were identified as meeting these criteria. Currently, there is no solid body of research on the primary prevention of PTSD to justify or guide interventions. The limitations and future directions of research in this domain are discussed.